How advertising works - Pereira, Francisco José Costa (2008)
Advertising, considered since ever as an intentional act of speech carried out by a transmitter and performed by the professional mediation of advertiser, emerges as the result of a strategic action with a pragmatic and very clear purpose: placing a brand in the consumer’s memory. In this context, advertising resorts mostly to strategies that act much more at level of emotions, sensations and the unconsciousness itself than at the rational level. Thus advertising founds itself on speech symbolism in detriment of information, in order to make the consumer recognize that the promoted brand offers him gratifications of sensorial, social and even intellectual order.